A Prophylactic multivalent vaccine to prevent acute infectious mononucleosis and EBV+ lymphomas - Foley, Joslyn Andrea (My University, 2021)
Infection with Epstein-Barr virus (EBV) has been associated with a number of diseases and is responsible for causing approximately 200,000 new cases of cancer each year globally. Despite imposing a significant health burden and more than 50 years of research since it’s discovery, no effective vaccine has been developed to prevent or treat EBV infection. The majority of proposed prophylactic EBV vaccines have relied on glycoprotein 350 (gp350) as the sole immunogen, but recently studies have demonstrated the importance of other proteins expressed on the surface of EBV, glycoproteins gB, gH, gL and gp42, that play a key role in entry into host cells. This study explored the combination of all five EBV surface glycoproteins implicated in viral entry as possible prophylactic immunogens. The Newcastle disease virus (NDV) virus-like particle (VLP) platform was used to express all of the glycoproteins simultaneously on the surface of a single biologically inert particle devoid of potentially oncogenic viral DNA and incapable of replication. The VLP was produced in a stable Chinese hamster ovary (CHO) cell line expressing gp350, gB, gp42, gL, and gH sequentially from a single DNA transcript and the cells were characterized by flow cytometry to confirm expression of each glycoprotein. These cells were transfected with NDV structural proteins matrix (M) and neucleoprotein (NP) to initiate VLP production and release into the supernatant. The VLP was purified from the supernatant by sucrose gradient centrifugation and characterized by immunoblot and ELISA. Rabbits were immunized with the VLP, TNE buffer, soluble gp350, UV-inactivated EBV, or a similar VLP expressing KSHV surface glycoproteins and antibodies specific to each of the five EBV glycoproteins was measured by ELISA. Animals immunized with the EBV-LP and UV-inactivated EBV (UV-EBV) had measurable antibody titers to all of the EBV glycoproteins, while animals immunized with gp350 only had gp350- specific antibodies. Neutralization activity was measured by incubating pooled serum from immunized rabbits with EBV-eGFP and assessing the infectivity of the serum:virus mixture in HEK-293T cells. Infected cells expressed eGFP and the percent of infected cells was measured by flow cytometry. Both the serum from EBV-LP and UV-inactivated EBV rabbits were able to achieve greater than 50% neutralization in HEK-293T cells. In conclusion, the EBV-LP immunogen designed, purified and characterized in this study was able to elicit binding and neutralizing antibodies against EBV, albeit at low levels. Thus, future work should focus on optimizing the expression levels of each protein, as well as mapping the neutralizing antibody activity obtained to direct further optimization of the EBV-LP.
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Master of Science in Medicine, 2021